2020
DOI: 10.28925/2663-4023.2020.8.97112
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Convolutional Neural Networks for the Security of the Object Recognition in a Video Stream

Abstract: The article is devoted to analyzing methods for recognizing images and finding them in the video stream. The evolution of the structure of convolutional neural networks used in the field of computer video flow diagnostics is analyzed. The performance of video flow diagnostics algorithms and car license plate recognition has been evaluated. The technique of recognizing the license plates of cars in the video stream of transport neural networks is described. The study focuses on the creation of a combined system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…На першому етапі вхідне зображення довільним чином розбивається на множину регіонів зацікавлення, які поступають на входи згорткових мереж (CNN, Convolution Neural Networks), які вирішують завдання місцезнаходження автономера на вхідному зображенні та формує на виході багатовимірний вектор ознак (4096 у нашому випадку). Отримані вектори ознак поступають на вхід класифікатора SVM (support vector machine,), лінійних класифікаторів на базі методу опорних векторів [14][15][16]. На виході Mask R-CNN нейромережі отримуємо місцеположення пластини автономера на фотозображенні автомобіля (рис.…”
Section: рис 2 пояснення принципу локалізації номера та його сегменunclassified
“…На першому етапі вхідне зображення довільним чином розбивається на множину регіонів зацікавлення, які поступають на входи згорткових мереж (CNN, Convolution Neural Networks), які вирішують завдання місцезнаходження автономера на вхідному зображенні та формує на виході багатовимірний вектор ознак (4096 у нашому випадку). Отримані вектори ознак поступають на вхід класифікатора SVM (support vector machine,), лінійних класифікаторів на базі методу опорних векторів [14][15][16]. На виході Mask R-CNN нейромережі отримуємо місцеположення пластини автономера на фотозображенні автомобіля (рис.…”
Section: рис 2 пояснення принципу локалізації номера та його сегменunclassified
“…(2) Convolutional neural network When studying cat cortex, convolutional neural network found that cat's visual system has a hierarchical structure similar to human cerebral cortex, while convolutional neural network is a hierarchical network, which has levels not found in traditional networks, and the functions and forms of layers have changed [9][10]. CNN is a kind of deep learning network structure widely used in image processing.…”
Section: Deep Learningmentioning
confidence: 99%